2020
DOI: 10.3389/fmars.2020.578717
|View full text |Cite
|
Sign up to set email alerts
|

The Celtic Sea Through Time and Space: Ecosystem Modeling to Unravel Fishing and Climate Change Impacts on Food-Web Structure and Dynamics

Abstract: Both trophic structure and biomass flow within marine food webs are influenced by the abiotic environment and anthropogenic stressors such as fishing. The abiotic environment has a large effect on species spatial distribution patterns and productivity and, consequently, spatial co-occurrence between predators and prey, while fishing alters species abundances and food-web structure. In order to disentangle the impacts of the abiotic environment and fishing in the Celtic Sea ecosystem, we developed a spatio-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 172 publications
(215 reference statements)
0
23
0
Order By: Relevance
“…The use of a generic spatial estimate of ocean productivity available to fish based on chlorophyll-a gradients and productivity fronts (OPFish) can allow advances in marine ecosystem science as (i) it provides a direct, observation-based and local estimate of secondary production in relative levels but comparable in space and time at the global scale (Druon et al, 2019(Druon et al, , 2021, (ii) it can identify pelagic feeding hotspots for the higher trophic levels in the last two decades and in real time and (iii) it can be used operationally to increase the robustness of species habitat and full ecosystem analyses (Hernvann et al, 2020). At this stage, the Harvest index relative to ocean productivity (H P index) may enhance awareness that local overfishing of the pelagic or demersal species community may be linked to excessive fishing pressure compared to local productivity.…”
Section: Perspectives For Research Management and Policymentioning
confidence: 99%
“…The use of a generic spatial estimate of ocean productivity available to fish based on chlorophyll-a gradients and productivity fronts (OPFish) can allow advances in marine ecosystem science as (i) it provides a direct, observation-based and local estimate of secondary production in relative levels but comparable in space and time at the global scale (Druon et al, 2019(Druon et al, , 2021, (ii) it can identify pelagic feeding hotspots for the higher trophic levels in the last two decades and in real time and (iii) it can be used operationally to increase the robustness of species habitat and full ecosystem analyses (Hernvann et al, 2020). At this stage, the Harvest index relative to ocean productivity (H P index) may enhance awareness that local overfishing of the pelagic or demersal species community may be linked to excessive fishing pressure compared to local productivity.…”
Section: Perspectives For Research Management and Policymentioning
confidence: 99%
“…The habitat analyses suggest that the horizontal gradient of chlorophyll-a is a better proxy than chlorophyll-a when seeking the spatial distribution of mesozooplankton and marine predators. We emphasise in this paper that, while this variable requires an advanced knowledge in ocean colour limitations, its availability would greatly help the marine biologist community to produce robust, observation-based, planktonto-fish indicators from local to global scale in nowcast and hindcast modelling, such as input data to develop more robust full ecosystem models (Hernvann et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the need for more regular trophic sampling as part of ecosystem surveys (e.g., Doray et al, 2018). However, this divergence in prey identified between the literature and SCA could also result from the sampling design, conducted during one season only and not covering the whole mosaic of environmental conditions and all species assemblages of the Celtic Sea (Hernvann et al, 2020). For instance, anglerfish's isotope signatures were consistent with substantial consumption of Norway lobster, whereas it was not identified as a putative prey in SCA data (Issac et al, 2017) but was observed in the predator's stomachs in a neighboring ecosystem at a different season (Crozier, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the environmental diversity characterizing the Celtic Sea (Hernvann et al, 2020; Walters et al, 2021), the generalist feeding behavior and ontogenetic diet shifts of some species (Day et al, 2019; Issac et al, 2017; Rault et al, 2017), the functional redundancy of several groups (Mérillet et al, unpublished manuscript), and benthic–pelagic coupling (Hernvann et al, 2020), data exhibited high intragroup variability and among‐group overlap in isotope signatures. Therefore, posterior distributions of dietary proportions were often diffuse, pointing out the limits of bulk SIA for studying such complex ecosystems.…”
Section: Discussionmentioning
confidence: 99%